(untitled) (Research, Society and Development, 2021)
Objective: The present study is related to a clinical case of whitening using the energy whitening technique in a devitalized aesthetic element Methodology: This is a clinical case report of descriptive analytical nature (Pereira et al., 2018). Case Report: Patient T.P.F, female, 41 years old, attended the Dentistry Clinic of Centro Universitário Fametro, with the main complaint “low self-esteem for having a tooth that is yellower than the others due to root canal treatment performed at around eight years of age”. In the anamnesis, the patient reported enjoying good health, no systemic diseases, no parafunctional habits, allergies and sensitivities to medications and foods. Conclusion: It is concluded that whitening by the immediate technique known as energy whitening, made the procedure safe and with a satisfactory result, improving the aesthetics of the smile and raising the patient’s self-esteem.